Leaning on air : a novel - Bostrom, Cheryl (Tyndale House Publishers, 2024)
They last spoke as teens...But on a country road twelve years later, a surprise encounter reunites ornithologist Celia Burke with veterinary surgeon Burnaby Hayes, and they plunge into the most unusual romance of her life. After a decade of marriage, Celia and Burnaby have found a unique and beautiful rhythm. Then tragedy strikes while Celia hunts for the nest of a research hawk near the Snake River. Reeling with grief, she's certain Burnaby won't understand her anguish or forgive the choice that initiated it. She flees to kindness at a remote farm in Washington's Palouse region, where a wild prairie and an alluring neighbor convince her to begin anew. But when unexplained accidents, cryptic sketches, and a mute little boy make her doubt her decision, only a red-tailed hawk and the endangered lives of those she loves can compel her to examine her past--and reconsider her future.